2005
DOI: 10.1177/0363546504272685
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Capsular Shift for Atraumatic Anterior-Inferior Shoulder Instability

Abstract: Results in this series demonstrate the efficacy and durability of a modified capsular shift procedure for the treatment of atraumatic anterior-inferior shoulder instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…The dominant side was involved in 269 (58%) of 468 shoulders, whereas the nondominant side was involved in 199 (42%) shoulders. These data was not reported in the remaining 393 shoulders 12,14,17,19,21,26,27,29,34 (Table 2). Patients were assessed at a median follow-up period of 4.2 years (ranging from 9 months 28 to 16 years 33 ).…”
Section: Demographicsmentioning
confidence: 91%
See 4 more Smart Citations
“…The dominant side was involved in 269 (58%) of 468 shoulders, whereas the nondominant side was involved in 199 (42%) shoulders. These data was not reported in the remaining 393 shoulders 12,14,17,19,21,26,27,29,34 (Table 2). Patients were assessed at a median follow-up period of 4.2 years (ranging from 9 months 28 to 16 years 33 ).…”
Section: Demographicsmentioning
confidence: 91%
“…Only 8 13,18,19,23,25,27,29,33 of 24 studies, describing 271 patients, also reported in their population individuals who underwent previous shoulder surgery for the management of MDI. Previous surgical procedures were performed in 71 (26%) of them: open capsular shift in 3 (4%), 13 laser-assisted capsular shrinkage in 10 (14%), 18 diagnostic arthroscopy in 2 (3%), 19 thermal capsulorrhaphy in 2 (3%), 23 and Bankart repair in 4 (6%).…”
Section: Previous Surgerymentioning
confidence: 99%
See 3 more Smart Citations